2014
DOI: 10.4103/0970-0358.146630
|View full text |Cite
|
Sign up to set email alerts
|

Laser: The torch of freedom for ankyloglossia

Abstract: The tongue is an important oral structure that affects speech, position of teeth, periodontal tissues, nutrition, swallowing, nursing, and certain social activities. Ankyloglossia or tongue-tie, is a congenital anomaly characterized by an abnormally short lingual frenulum, which restricts mobility of the tongue. Though the ankyloglossia is not a serious condition, it may lead to a host of problems including infant feeding difficulties, speech disorders, and various mechanical and social issues related to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Barot et al reported very positive results after a frenectomy with laser technology (wavelength: 810 nm; fiber diameter: 200 µm used in direct contact with the tissue; power 2 W in a continuous mode and a focused beam). Through this protocol, the authors achieved complete healing, an increase of >16 mm in tongue mobility and speech improvement after therapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barot et al reported very positive results after a frenectomy with laser technology (wavelength: 810 nm; fiber diameter: 200 µm used in direct contact with the tissue; power 2 W in a continuous mode and a focused beam). Through this protocol, the authors achieved complete healing, an increase of >16 mm in tongue mobility and speech improvement after therapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Derikvand et al [40] have demonstrated positive factors of using laser technology in terms of healing and postoperative complications. Furthermore, Barot et al [41] reported an improvement in tongue mobility and speech in patients treated with a laser. The absence of traditional surgical instruments and the hemostatic effect of the laser allow for bloodless surgeries without the need for sutures, which would be uncomfortable during the postoperative period, especially when performing myofunctional exercises.…”
Section: Discussionmentioning
confidence: 98%
“…The tongue should not be blanched when retruded anteriorly. A diastema between the mandibular central incisors should not be produced by the lingual frenum [7].…”
Section: Discussionmentioning
confidence: 99%